2007
DOI: 10.1007/s00436-007-0808-0
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of subtype 3 among Blastocystis isolates from a major hospital in Singapore

Abstract: Blastocystis is an enteric protozoan parasite commonly found in humans and animals. Phylogenetic and genotypic analyses have shown that Blastocystis exhibits extreme genetic diversity, and humans are host to a number of zoonotic isolates. In the present study, the prevalence of Blastocystis in 276 stool samples from a hospital in Singapore was examined, and for the first time, riboprinting using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) was used to determine the genetic dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
105
3
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(123 citation statements)
references
References 33 publications
11
105
3
3
Order By: Relevance
“…There was a 78% incidence of ST3 and a 22% incidence of ST1. This prevalence of ST3 in humans in an urbanised area such as Singapore is consistent with the argument that ST3 is of human origin [38].…”
Section: Epidemiologysupporting
confidence: 87%
“…There was a 78% incidence of ST3 and a 22% incidence of ST1. This prevalence of ST3 in humans in an urbanised area such as Singapore is consistent with the argument that ST3 is of human origin [38].…”
Section: Epidemiologysupporting
confidence: 87%
“…Many epidemiologic studies reported only further use of molecular analysis if there are samples positive by culture. 4,17,24,[28][29][30] An obvious conclusion is that these studies did not provide a true representation of the prevalence of Blastocystis infections in human population studies where some culture systems used may not enable certain strains of Blastocystis to grow.…”
Section: Discussionmentioning
confidence: 98%
“…1 Blastocystis is the most common parasite isolated from human stool samples in developing and developed countries. 2,3 Rates of infection vary from 3.3% in developed countries 4 to 53.8% in developing countries. 5 Blastocystis is found in humans and animals.…”
Section: Introductionmentioning
confidence: 99%
“…An apparently higher prevalence of the mixed infection of subtypes in this community also supported and strengthened the possibility of person-to-person transmission when compared with the prevalence of Blastocystis infection in other studies (20% versus 1.1-14.3%). [28][29][30] Zoonotic transmission of Blastocystis in this population could be possible. Multivariate analysis showed that the girls who did not wash their hands after contacting pets had a high risk of getting Blastocystis infection.…”
Section: 11-15mentioning
confidence: 92%